2012
DOI: 10.1096/fj.12-209460
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase Gem and its partner Kif9 are required for chromosome alignment, spindle length control, and mitotic progression

Abstract: Within the Ras superfamily, Gem is a small GTP-binding protein that plays a role in regulating Ca(2+) channels and cytoskeletal remodeling in interphase cells. Here, we report for the first time that Gem is a spindle-associated protein and is required for proper mitotic progression. Functionally, loss of Gem leads to misaligned chromosomes and prometaphase delay. On the basis of different experimental approaches, we demonstrate that loss of Gem by RNA interference induces spindle elongation, while its enforced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…GEM belongs to the Ras superfamily of small GTPases that are involved in various intracellular pathways. [33][34][35] Studies have demonstrated that GEM contributes to cell invasion, 36 mitotic progression, 37 and actin remodeling. 38 In addition, GEM has been reported to be an adverse prognostic factor in patients with bladder carcinoma 39 and upregulated in mutant ALK-expressing neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…GEM belongs to the Ras superfamily of small GTPases that are involved in various intracellular pathways. [33][34][35] Studies have demonstrated that GEM contributes to cell invasion, 36 mitotic progression, 37 and actin remodeling. 38 In addition, GEM has been reported to be an adverse prognostic factor in patients with bladder carcinoma 39 and upregulated in mutant ALK-expressing neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…GEM is a small GTP-binding protein that plays a role in regulating Ca 2+ channel expression at the cell surface [30]. Furthermore, it is involved in cytoskeletal remodeling in interphase cells and is a spindle-associated protein required for prober mitotic progression [31]. EDNRA is a G-protein coupled receptor for endothelins and it is expressed on vascular smooth-muscle cells and on heart, kidney, and neuronal cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…These tissues can contain primary cilia, however, and the low levels of KIF9 could reflect a potential function in primary cilia. In addition, KIF9 has been reported to be important for matrix degradation in macrophages [1] as well as interacting with GEM with possible functions in spindle control [2,17]. The low levels of signal detected in tissues that do not have multiciliated cells may reflect such alternative functions.…”
Section: Discussionmentioning
confidence: 99%
“…A pair of gRNAs targeting intron 2 (gRNAE22) and intron 3 (gRNAE23) of KIF9 gene respectively were designed using an online tool (https://benchling.com/) and generated by in vitro transcription [1] (Table 1 and Figure 1). Cas9 protein was purchased from PNA Bio Inc. A KIF9 conditional knockout(CKO) HRD plasmid carrying around 2kb homologous arms on each side surrounding a floxed KIF9 exon3 with an added primer sequence (KS) for genotyping (Supplementary Data 1) was generated by SLiCE cloning [2]. Superovulated female C57BL6 mice (3-4 weeks old) were mated to C57BL6 males, and fertilized embryos were collected from oviducts.…”
Section: Generation Of Floxed Kif9 Micementioning
confidence: 99%
See 1 more Smart Citation